P081 An audit of the management and aetiology of proctitis in men who have sex with men (MSM). (30th June 2016) - Gardner, Dean; French, Patrick
Abstract : Background: Proctitis remains an important presentation of MSM to sexual health clinics. It causes significant morbidity and facilitates the transmission of other infections including HIV. Aims: To audit the management and aetiology of proctitis in a UK sexual health clinic and determine the pattern of STIs presenting with rectal symptoms. Methods: 100 consecutive notes of MSM presenting with rectal symptoms were examined (December 2014 – March 2015). The local clinical management standard is proctoscopy and Gram stain for gonorrhoea; gonorrhoea culture; gonorrhoea/chlamydia NAAT; HSV1/HSV2/ T.pallidum PCR; syphilis serology. Positive chlamydia NAATs are tested for LGV-associated serovars. Results: 88/100 had proctoscopy performed. The tests undertaken and test results are summarised in the table below. 43 patients had all the recommended tests. 66 infections were diagnosed in 53 patients. 42 patients had one infection, 9 had two infections and 2 had three infections. 35 patients were diagnosed HIV positive before presentation, 64 patients tested HIV negative at presentation and one patient declined testing. Discussion: This audit confirms that the majority of MSM presenting with rectal symptoms had proctoscopy but there is room for improvement in practice as only a minority had all tests undertaken. STIs are a common cause of anal symptoms in MSM and this data strongly supports a low threshold for STI screening. Routine HSV testing in MSM with rectal symptoms is useful.